Analyzing Student Perceptions of the Effectiveness of Project-Based Learning in the Department of Mathematics and Sciences Education at the University of Mataram - Alia Cahyani; Maria Anastasia Da Lopez; Ziadatun Nikmatillah; Gunawan Gunawan (Indonesian Publication Center, 2025)
This study examines students’ perceptions of Project-Based Learning (PjBL) implementation, focusing on the perceived benefits, support needs, and challenges among pre-service teachers in the Department of Mathematics and Natural Sciences Education, University of Mataram. Data were collected through a survey of 64 respondents. The results indicate that the majority of students perceived PjBL as beneficial for enhancing conceptual understanding, creativity, collaboration, and problem-solving skills. Notably, 98.4% of respondents supported the continuous implementation of this model. Key support requirements identified include step-by-step guidance, project examples, and adequate references. Meanwhile, the primary challenges involved time management, group dynamics, facility limitations, and supervision intensity. The study concludes that while PjBL is effective in developing prospective teachers' competencies, its implementation demands more structured planning and consistent supervision to optimize outcomes.